2016
DOI: 10.1155/2016/5320641
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the cAMP/PKA/CREB Pathway Contributes to the Analgesic Effects of Electroacupuncture in the Anterior Cingulate Cortex in a Rat Pain Memory Model

Abstract: Pain memory is considered as endopathic factor underlying stubborn chronic pain. Our previous study demonstrated that electroacupuncture (EA) can alleviate retrieval of pain memory. This study was designed to observe the different effects between EA and indomethacin (a kind of nonsteroid anti-inflammatory drugs, NSAIDs) in a rat pain memory model. To explore the critical role of protein kinase A (PKA) in pain memory, a PKA inhibitor was microinjected into anterior cingulate cortex (ACC) in model rats. We furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…Regarding EA analgesia and its mechanism in treating inflammatory pain, several studies have focused on the analgesic effect of EA on the sensory-discriminative aspect of pain [ 18 21 ]; however, few studies have examined the effect and mechanisms of EA on the emotional-affective dimension of pain. A growing number of studies have indicated that EA can relieve pain-related anxiety [ 13 , 14 ] through a mechanism that involves opioid receptor activation in the ACC [ 32 ]. However, the mechanisms underlying the effects of EA on inflammatory pain-related anxiety are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding EA analgesia and its mechanism in treating inflammatory pain, several studies have focused on the analgesic effect of EA on the sensory-discriminative aspect of pain [ 18 21 ]; however, few studies have examined the effect and mechanisms of EA on the emotional-affective dimension of pain. A growing number of studies have indicated that EA can relieve pain-related anxiety [ 13 , 14 ] through a mechanism that involves opioid receptor activation in the ACC [ 32 ]. However, the mechanisms underlying the effects of EA on inflammatory pain-related anxiety are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the mechanism and treatment of psychiatric disorders associated with chronic pain have received increasing attention. Previous studies by our laboratory and others have reported that EA can significantly reduce the anxiety-like behaviors associated with chronic pain [ 13 , 14 ]. However, the mechanism for these effects is unclear.…”
Section: Introductionmentioning
confidence: 98%
“… 7 9 Recently, a significant number of preclinical research groups have focused their attention on the affective symptoms of pain. 10 12 The conditioned-place aversion (CPA) paradigm is a highly sensitive method for measuring the negative effect of an aversive memory associated with a pain-paired context. 13 16 Recent studies have shown that the affective component of chronic inflammatory pain can be assessed with a CPA test (pain aversion) and other emotional behavior tests, such as the elevated zero maze (EZM) and open field (OF) tests.…”
Section: Introductionmentioning
confidence: 99%
“…However, how EA regulates 5-HT 7 R remains unclear. Electroacupuncture was reported to reduce the cytoplasmic content of cAMP [26]. Decreased cAMP affects the phosphorylation of PKA and ERK 1/2 [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation found EA shows a direct effect on nociceptive neurons [23,24]. In addition, several studies [25][26][27] suggested PKA and ERK 1/2 in the spinal dorsal horn might involve EA antihyperalgesia.…”
Section: Introductionmentioning
confidence: 94%